Fe-based nanocrystalline alloy and its manufacturing method
By synthesizing a specific composition Fe-based nanocrystalline alloy and using rapid cooling and heat treatment technology, the problems of high magnetic loss and low saturation permeability of existing Fe-based nanocrystalline alloys in high frequency and high power applications are solved, achieving efficient magnetic performance and good thermal performance.
Patent Information
- Application Number
- JP2022572665
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-01
- Filing Date
- 2022-02-16
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2042-02-16
AI Technical Summary
The existing Fe-based nanocrystalline alloys have problems with high magnetic loss and low saturation permeability in high frequency and high power applications, and are costly, which limits its wide application.
By synthesizing an alloy of Fe (100-a-b-c-d-e-f) B a Si b P c C d Cu e Nb f, where 8≦a≦12, 0.2≦b≦6, 2.0≦c≦6.0, 0.5≦d≦4, 0.6≦e≦1.3, 0.6≦f≦0.9, and 1≦e/f≦1.4, and Fe-based nanocrystalline alloys with excellent soft magnetic properties were prepared using rapid cooling and heat treatment technology.
The high saturation permeability (≥1.75T) and low magnetic loss (<0.30W/kg) of Fe-based nanocrystalline alloy are achieved, which is suitable for industrial manufacturing.
Smart Images

Figure 0007649325000010 
Figure 0007649325000011 
Figure 0007649325000012
Abstract
Description
[Technical field]
[0001] This application claims priority to Chinese Patent Application No. 202110224190.5, entitled "Fe-based Amorphous Nanocrystalline Alloy and Preparation Method thereof," filed with the State Intellectual Property Office on March 1, 2021, the contents of which are incorporated herein by reference.
[0002] The present specification relates to the technical field of magnetic materials, in particular Fe-based Nanocrystals The present invention relates to an alloy and a method for producing the same. [Background technology]
[0003] Currently, soft magnetic materials used in transformers, motors or generators, current sensors, magnetic sensors, and pulse power magnetic components include silicon steel, ferrite, Co-based amorphous alloys, and nanocrystalline alloys. Among these soft magnetic materials, silicon steel is inexpensive and has high magnetic flux density and machinability, but is prone to high losses under high frequencies. Ferrite has limited applications in high-power, high-saturation magnetic induction scenarios due to its low saturation magnetic flux density. Co-based amorphous alloys are not only expensive, but also have low saturation magnetic flux density, so when used as high-power devices, the Co-based amorphous alloys are thermodynamically unstable and prone to high losses during use.
[0004] Fe-based amorphous alloys are ideal magnetic materials because they have the advantages of high saturation magnetic flux density and low loss under high power. Currently, Fe-based amorphous / nanocrystalline alloys are available as Finemet (Fe 73.5 S 13.5Finemet alloys have been developed into three main systems: B9Cu1Nb3), Nanoperm (Fe-MB, M=Zr, Hf, Nb, etc.), and HITPERM (Fe-Co-MB, M=Zr, Hf, Nb, etc.). Among them, Finemet alloys have been widely used in many fields due to their good soft magnetic properties and low cost. However, Finemet alloys have low saturation induction (only about 1.25 T). Compared with silicon steels with high saturation induction, Finemet alloys require a larger volume under the same conditions for application, which severely limits the applications of Finemet alloys. In addition, compared with silicon steels, Finemet alloys are expensive due to the presence of Nb, a rare metal, and do not contribute to social development. Summary of the Invention
[0005] The embodiments herein include Fe-based Nanocrystals The present invention provides an alloy and a method for producing the same. Nanocrystals The alloy has very good soft magnetic properties and is suitable for industrial production.
[0006] In a first aspect, embodiments herein provide a Fe-based ferroelectric material having an atomic percentage of elements according to formula (1): Nanocrystals Provide an alloy, Fe (100-a-b-c-d-e-f) B a S b P c C d Cu e Nb f (1) wherein 8≦a≦12, 0.2≦b≦6, 2.0≦c≦6.0, 0.5≦d≦4, 0.6≦e≦1.3, 0.6≦f≦0.9, and 1≦e / f≦1.4.
[0007] In some embodiments, the Fe group Nanocrystals The alloy is in the form of a continuous thin strip, and the strip thickness of the thin strip is 30 μm or more. In some embodiments, the Fe group Nanocrystals The temperature difference between the second crystallization onset temperature and the first crystallization onset temperature of the alloy is greater than 120°C.
[0008] In some embodiments, the ratio of the temperature difference to the first exotherm is 1.38 or greater, and the first exotherm is the amount of heat generated by the first crystallization of the Fe group. Nanocrystals The amount of heat released from the alloy, the unit of the temperature difference is Celsius, and the unit of the first heat amount is J / g.
[0009] In some embodiments, the Fe group Nanocrystals The saturation magnetic induction of the alloy is 1.75T or more, and the Fe-based alloy is Nanocrystals The core loss per unit weight of the alloy is less than 0.30 W / kg, which is the same as that of the Fe-based alloy. Nanocrystals The size of the nanograins in the alloy is 20-30 nm.
[0010] In a second embodiment, the Fe group as described in the first embodiment is Nanocrystals The method for producing the alloy comprises the steps of: (a) blending the elements according to the atomic percentages shown in formula (1) and then smelting to obtain molten steel; (b) subjecting the molten steel to single-roll quenching to obtain an initial strip; (c) heating the initial strip to a first preset temperature that is 20-30° C. higher than a first crystallization onset temperature of the initial strip; (d) maintaining this temperature for 30 to 40 minutes; and (e) The initial strip is cooled and the Fe-based Nanocrystals Obtaining an alloy, Including, Fe (100-a-b-c-d-e-f) B a S b P c C d Cu e Nb f (1) where 8≦a≦12, 0.2≦b≦6, 2.0≦c≦6.0, 0.5≦d≦4, 0.6≦e≦1.3, 0.6≦f≦0.9, and 1≦e / f≦1.4.
[0011] In some embodiments, heating the initial strip to a first preset temperature comprises: heating the initial strip to a second preset temperature lower than the first preset temperature and holding the second preset temperature for a preset time; and heating the initial strip from the second preset temperature to the first preset temperature at a first preset heating rate.
[0012] In some embodiments, the second preset temperature is 280° C., the preset time is 2 hours, and the first preset heating rate is 30° C. / min. In some embodiments, in step (e), the initial strip is cooled at a cooling rate of 50° C. / sec.
[0013] In a fourth embodiment, the Fe group as described in the first embodiment is Nanocrystals A magnetic component constructed from the alloy is provided. The Fe group provided by the embodiment of the present specification Nanocrystals The alloy has good magnetic properties, very good thermal properties, and a wide crystallization temperature zone, and is therefore suitable for industrial production. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 illustrates a process flow for Fe-based nanocrystalline alloys provided by embodiments herein. [Diagram 2] FIG. 2 shows the XRD patterns of embodiments 1, 2, and 3, where 1 represents embodiment 1, 2 represents embodiment 2, and 3 represents embodiment 3. [Diagram 3] FIG. 3 shows the XRD patterns of embodiments 6, 7, and 8, where 6 represents embodiment 6, 7 represents embodiment 7, and 8 represents embodiment 8. [Figure 4] FIG. 4 shows the XRD patterns of embodiments 12, 13, and 14, where 12 represents embodiment 12, 13 represents embodiment 13, and 14 represents embodiment 14. [Diagram 5] FIG. 5 shows the DSC patterns of embodiments 1, 3, and 6, where 1 represents embodiment 1, 3 represents embodiment 3, and 6 represents embodiment 6. [Figure 6] FIG. 6 shows the DSC patterns of Embodiments 2, 8, 12, and 14, where 2 represents Embodiment 2, 8 represents Embodiment 8, 12 represents Embodiment 12, and 14 represents Embodiment 14. DETAILED DESCRIPTION OF THE INVENTION
[0015] The technical scheme in the embodiments of the present invention will be described below with reference to the accompanying drawings. It is obvious that the described embodiments are merely exemplary embodiments and not all possible embodiments of this specification.
[0016] One scheme provides an Fe-based amorphous alloy Fe a B b Si c P x C y Cu z where 79 ≦ a ≦ 86 atomic %, 5 ≦ b ≦ 13 atomic %, 0 < c ≦ 8 atomic %, 1 ≦ x ≦ 8 atomic %, 0 ≦ y ≦ 5 atomic %, 0.4 ≦ z ≦ 1.4 atomic %, and 0.08 ≦ z / x ≦ 0.8. By using the Fe-based amorphous alloy as the initial component, an Fe-based nanocrystalline alloy having both high saturation magnetic induction and high magnetic permeability can be obtained. In order to crystallize and refine the Fe-based amorphous alloy to the nanoscale, the Fe-based amorphous alloy needs to be heated at a high heating rate of 100 ° C. / min, and the temperature obtained after heating must be maintained within a narrow temperature range of 30 to 40 ° C. Therefore, it is extremely difficult to manufacture a nanocrystalline alloy based on the Fe-based amorphous alloy in the industrial field. In addition, near the set temperature, a large amount of heat is immediately generated due to crystallization, which causes a rapid increase in the temperature of large components, and as a result, continuous temperature increase and even melting occur.
[0017] According to the embodiment of this specification, the second crystallization start temperature (T x2 ) and the first crystallization start temperature (T x1) is widened by controlling the composition, the window of the heat treatment process of crystallization is expanded, and the problem that the heat treatment temperature of the strip exceeds the second crystallization temperature due to the excessive heat Q1 released from the alloy during the first crystallization process, resulting in the strip burning due to the continuous temperature increase, is solved.
[0018] In the embodiment of the present specification, the heat treatment characteristic evaluation parameter κ is set as follows.
[0019]
number
[0020] Through the above exploration, the present embodiment provides a Fe-based Nanocrystalline Alloys Fe (100-a-b-c-d-e-f) B a S b P c C d Cu e Nb f where a, b, c, d, and e each represent the atomic percentage of the corresponding component, and 8≦a≦12, 0.2≦b≦6, 2.0≦c≦6.0, 0.5≦d≦4, 0.6≦e≦1.3, 0.6≦f≦0.9, and 1≦e / f≦1.4.
[0021] As an essential element, Fe can improve the saturation magnetic induction and reduce the material cost. If the Fe content is lower than 78 atomic %, the desired saturation magnetic induction cannot be obtained. If the Fe content is higher than 86 atomic %, it is difficult to form an amorphous phase, and coarse α-Fe crystal grains will be formed by the quenching method. As a result, a uniform nanocrystalline structure cannot be obtained, leading to a deterioration of the soft magnetic properties.
[0022] As an essential element, B can improve the amorphous forming ability. When the B content is lower than 5 atomic %, it is difficult to form an amorphous phase by the quenching method. When the B content is higher than 12 atomic %, T x2 and T x1 The difference between (ΔT=T x2 -T x1 ) decreases, which is not conducive to the formation of a uniform nanocrystalline structure, resulting in a deterioration of the soft magnetic properties.
[0023] Si can inhibit the precipitation of Fe and B compounds in the crystallized nanocrystalline structure, thus stabilizing the nanocrystalline structure. When the content of Si is more than 8 atomic %, the saturation magnetic induction and amorphous forming ability are reduced, and as a result, the soft magnetic properties are reduced. In particular, when the content of Si is more than 0.8 atomic %, the amorphous forming ability is improved, and thin strips can be stably and continuously produced. In addition, a uniform nanocrystalline structure can be obtained by increasing ΔT.
[0024] As an essential element, P can improve the amorphous forming ability. If the P content is less than 1 atomic %, it is difficult to form an amorphous phase by quenching. If the P content is more than 8 atomic %, the saturation magnetic induction and soft magnetic properties will be reduced. In particular, if the P content is 2 to 5 atomic %, the amorphous forming ability can be improved.
[0025] C can enhance the amorphous forming ability, and the addition of C can reduce the metalloid content and reduce the material cost. If the C content exceeds 5 atomic %, embrittlement will be caused, and as a result, the soft magnetic properties will deteriorate. In particular, if the C content is less than 3 atomic %, segregation caused by the volatilization of C can be suppressed.
[0026] Cu contributes to the formation of numerous fcc-Cu clusters and bcc-(Fe) crystal nuclei in the quenching process, and also promotes the precipitation of bcc-(Fe) crystal nuclei in the heat treatment process, thereby improving the saturation magnetic induction. When the Cu content is less than 0.6 at.%, it is disadvantageous to nanocrystallization. When the Cu content is more than 1.4 at.%, the amorphous phase becomes non-uniform, which is not conducive to the formation of a uniform nanocrystalline structure, and as a result, the soft magnetic properties are deteriorated. It should be noted that when the brittleness of nanocrystalline alloys is considered, the Cu content should be controlled to less than 1.3 at.%. In addition, it is desirable to provide the alloy with a wider crystallization temperature zone (i.e., T x2 ~T x1 In order to form a nanocrystalline structure with small grain size and uniform distribution in the temperature range of κ, it is necessary to add certain large atoms to inhibit abnormal growth of grains. The ratio of Cu atoms to Nb atoms, i.e., the value of e / f, can be indicated as λ. The inventors of the present invention have confirmed through numerous experiments that when 1≦λ≦1.4, nanocrystalline alloys and stable grain sizes can be obtained through a wide heat treatment range (κ≧1.38).
[0027] As a large atom, Nb can improve the amorphous forming ability of the alloy, inhibit the precipitation of the main crystalline phase in the amorphous precursor, as well as inhibit the excessive growth of atoms and control the grain size during heat treatment. The addition of Nb improves the thermal stability of the amorphous phase, thus increasing the nucleation activation energy and growth activation energy of the main crystalline phase α-Fe. The atomic content of Nb is controlled to be 0.6-0.9 atomic %.
[0028] Referring to FIG. 1, a scheme provided by an embodiment herein may include the following steps. 1. Blend The blend contains Fe (100-a-b-c-d-e-f) B a S b P c C d Cu e Nb fThe required industrial raw materials are pure Fe, pure Cu, elemental Si, pure C, and Fe-B and Fe-P alloys, and the purity of the raw materials is shown in Table 1.
[0029] [Table 1]
[0030] 2. Smelting The raw materials may be weighed according to mass ratio and then put into a heating furnace (specifically, a medium frequency induction heating furnace) for melting. During the melting process, an inert gas (such as argon) is introduced as a protective gas, and after melting, the materials are left to stand for 30 minutes to ensure that the composition of the molten steel is uniform without segregation.
[0031] 3. Single roll quenching for strip production Amorphous alloy strips can be produced by the copper roll quenching method, i.e., molten steel is poured at 1400-1500°C and quenched by the copper roll quenching method. Amorphous alloy strip was obtained and produced Amorphous alloy strip is wound into a loop. By way of example, the inner diameter of the loop may be 65 mm and the outer diameter may be 70 mm. In the embodiments herein, the thin strip may also be referred to as a strip.
[0032] 4.Heat treatment The amorphous alloy strip produced above can be subjected to a heat treatment, which may also be referred to as a crystallization annealing treatment. NanocrystalsThe purpose is to promote the amorphous alloy to generate nanoscale crystal grains so that an alloy is produced. Specifically, during heat treatment or crystallization annealing, a temperature 20-30°C higher than the first crystallization start temperature of the amorphous alloy is set as the heating target temperature. For example, the heating target temperature can be 420°C. For example, in order to ensure a uniform temperature increase, the heat treatment process of the amorphous alloy is divided into two stages. In the first stage, the temperature of the amorphous alloy thin strip is increased to 280°C and this temperature is held for 2 hours. In the second stage, the temperature of the amorphous alloy thin strip is increased to the heating target temperature at a rate of 30°C / min and this temperature is held for 30-40 minutes. Finally, the temperature is decreased at a rate of 50°C / sec, and after cooling to room temperature, Nanocrystals The alloy strip can be obtained. In order to prevent oxidation during the heat treatment, the heat treatment process is carried out in an inert gas (such as argon) atmosphere.
[0033] 5. Performance test, specifically, obtained Nanocrystals Performance evaluation and analysis of alloy strips (1) Measurement of saturation magnetic induction and coercivity. Nanocrystals The saturation magnetization strength Bs of the alloy strip is measured using a vibrating sample magnetometer (VSM). Nanocrystals The coercive force of the alloy strip is measured by a soft magnetic DC tester. Based on the principle of electromagnetic induction, the VSM obtains a curved relationship between the magnetic moment of the sample and the external magnetic field, and the range of the test magnetic field is -12500~12500 Oe. Before the test, the instrument is calibrated with a prepared Ni standard, and then the magnetic sample to be tested is crushed, followed by taking about 0.032 g of the sample, wrapping it tightly in tin foil, and placing it into a copper mold for measurement.
[0034] (2) Measurement of loss power and excitation power. A BH tester is used for the measurement. By setting the sample parameters (effective magnetic circuit length, effective cross-sectional area, number of turns, etc.) and test conditions (test frequency, magnetic field strength, maximum magnetic flux density, maximum induced voltage, etc.), a BH curve is output and various magnetic property parameters are tested. Loss power (Ps) and excitation power (Ss) are the most important of all the parameters.
[0035] 6. XRD / DSC analysis, specifically the detection and analysis of amorphous alloy strips before heat treatment (1) X-ray diffraction (XRD) is used to verify whether the manufactured amorphous alloy strip has a completely amorphous structure. In order to confirm that the alloy strip has a completely amorphous structure, the XRD patterns of all samples are obtained from the free side of the alloy strip (opposite to the copper roll surface). The relevant test conditions and parameters are: a graphite monochromator with X-ray wavelength is used for filtering, the tube voltage is 40 kV, the tube current is 30 mA, the test range is 20-90°, the step length is 0.02°, and the scan speed is 8° / min. The amorphous alloy strip in this application can be identified by the XRD pattern. When the characteristic spectrum shows a broad diffraction peak (also called the "steamed bread peak"), it can be concluded that the strip has a completely amorphous structure.
[0036] (2) Thermal analysis of the amorphous alloy strip is carried out by differential scanning calorimetry (DSC) to test the crystallization behavior and thermal stability of the alloy strip. Before the test, the strip is cut into small pieces with an area of less than 1 mm x 1 mm, and a small piece of about 20 mg of the strip is obtained, and the sample is placed on the sample table in an alumina crucible and heated at a heating rate of 20 ° C / min from room temperature to 300-800 ° C, preferably to 800 ° C, under the protection of N2. By analyzing the DSC curve of the sample, the phase transition of each sample during heating can be obtained, and the thermal characteristic temperature parameters such as the Curie temperature Tc, glass transition temperature Tg, and crystallization start temperature Tx of the alloy strip can be obtained. According to the characteristic temperature value of the DSC curve of the alloy strip, the thermal stability of the alloy strip can be reflected, thereby obtaining a basis for determining the heat treatment process of the amorphous strip. The approximate annealing temperature range is determined. The initial crystallization temperature of the first stage of the alloy strip is T x1 (i.e., the temperature point at which α-Fe(Si) begins to precipitate), and the initial crystallization temperature of the second stage is T x2 (i.e., the temperature point at which the Fe-(B,P) compound begins to precipitate), and the difference between these two initial crystallization temperatures is ΔT x (ΔT x =T x2 -T x1 )
[0037] The schemes provided herein are now demonstrated along with specific embodiments. I. Verification of Cu's role and scope of control In different embodiments, different amounts of Cu are added to control the Cu content in the alloy to study the effect of Cu and the heat treatment characteristic parameters κ and T max The alloy compositions (contents of each component are expressed in atomic percent) of the embodiments and comparative examples are shown in Table 2.
[0038] The amorphous alloy strip can be manufactured and subjected to heat treatment according to the scheme shown in FIG. 1, which includes the following steps: 11. Blend The blends were made according to the compositions of each embodiment and comparative example shown in Table 2. The industrial raw materials required were pure Fe, pure Cu, elemental Si, pure C, and Fe-B and Fe-P alloys, and the purity of the raw materials is shown in Table 1.
[0039] 12. Smelting The raw materials were weighed according to mass ratio and then put into a heating furnace (specifically, a medium frequency induction heating furnace) for melting. During the melting process, inert gas (such as argon) was introduced as a protective gas, and after melting, the materials were left to stand for 30 minutes to ensure that the composition of the molten steel was uniform without segregation. In one example, the total mass of the raw materials was 200 kg.
[0040] 13. Single-roll quenching for strip production The amorphous alloy strip is produced by the copper roll quenching method, that is, the molten steel is poured at 1400-1500°C and then quenched by the copper roll quenching method. Amorphous Alloys Strips were obtained and manufactured Amorphous Alloys The strip was wound into a loop. By way of example, the inner diameter of the loop may be 65 mm and the outer diameter may be 70 mm. In the embodiments herein, the thin strip may also be referred to as a strip.
[0041] 14.Heat treatment The amorphous alloy strips produced above were subjected to a heat treatment, which may also be referred to as a crystallization annealing treatment. NanocrystalsThe purpose is to promote the amorphous alloy to generate nanoscale crystal grains so that an alloy is produced. Specifically, during the heat treatment or crystallization annealing, a temperature 20-30°C higher than the first crystallization start temperature of the amorphous alloy is set as the heating target temperature. For example, the heating target temperature can be 420°C. For example, in order to ensure a uniform temperature increase, the heat treatment process of the amorphous alloy is divided into two stages. In the first stage, the temperature of the amorphous alloy thin strip is increased to 280°C and held at this temperature for 2 hours. In the second stage, the temperature of the amorphous alloy thin strip is increased to the heating target temperature at a rate of 30°C / min and held at this temperature for 30-40 minutes. Finally, the temperature is decreased at a rate of 50°C / sec, and after cooling to room temperature, Nanocrystals The alloy strip can be obtained. In order to prevent oxidation during the heat treatment, the heat treatment process is carried out in an inert gas (such as argon) atmosphere.
[0042] In this manner, strips of each of the embodiments or comparative examples in Table 2 were produced. Using the XRD analysis described above, Nanocrystals We verified whether the alloy strip had a completely amorphous structure. The verification result is shown in Figure 2, which shows that only one broad diffuse scattering peak appeared at about 45°, indicating that the alloy sample had a completely amorphous structure.
[0043] The results of the DSC analysis are shown in Table 2. Two obvious exothermic peaks appeared in the DSC curve of the sample, and the onset temperatures of the first and second exothermic peaks were T x1 and T x2 Based on these, ΔT x The area of the first exothermic peak can be calculated, so that the heat release Q1 of the alloy during the first crystallization can be calculated, and then the heat treatment characteristic parameter κ can be obtained.
[0044] [Table 2]
[0045] ΔT with different Cu contents x The effect of Cu on ΔT can be seen from Table 2. In the range of 0.6 to 1.3 atomic %, the Cu content increases with increasing x gradually increased (from 120°C to 142°C), i.e., the heat treatment window increased obviously. Based on the amount of heat Q1 released from the first crystallization peak, the heat treatment characteristic parameter κ was calculated, and the minimum value of κ was 1.38. After the ten strips were stacked, the maximum temperature T after the continuous temperature increase of the first crystallization of each embodiment was max The T of each embodiment was measured. max is the second crystallization temperature T x2 It can be seen that the maximum temperature T after the first crystallization was increased continuously was not exceeded. max means the maximum temperature of the alloy under the action of the heat released during the first crystallization process (i.e., Q1).
[0046] Embodiments 4 and 5 are characterized by different contents of B, Si, P, and C. Nanocrystals The effect on the thermal properties of the alloy is shown. As shown in Table 2, the contents of B, Si, P, and C have little effect on the thermal properties. Nanocrystals The thermal properties of the alloy are primarily affected by the Cu content.
[0047] From the comparative examples, it can be seen that when the Cu content was less than 0.6 atomic % or more than 1.3 atomic %, the values of λ were 0.5, 1.87, and 1.25, respectively. In this case, ΔT x The maximum value of T was 102°C, and the heat treatment characteristic parameter κ was 1.11 or less. max were all above the onset temperature of the second crystallization because the first crystallization released a large amount of heat, which triggered the second crystallization peak, leading to a continuous increase in temperature until the sample burned.
[0048] The amorphous alloy strip was subjected to heat treatment and performance test, and the specific process can be referred to the above. The performance test results are shown in Table 3. After heat treatment, the saturation magnetic induction and coercive force were measured, and then the magnetic properties of the loop (under the excitation condition of 1.5T / 50Hz) were measured by a BH tester. The iron loss per unit weight is Ps, and the unit excitation power is Ss. The crystal grain size was calculated using XRD analysis software.
[0049] [Table 3]
[0050] From Table 3, it can be seen that the saturation magnetic induction Bs of the embodiments 1 to 5 was 1.75 T or more. When the Cu content was within the range of 0.6 to 1.3 atomic %, the iron loss Ps per unit weight of the embodiments after heat treatment was clearly lower than that of the comparative example, and the unit excitation power Ss of the embodiments was also lower than that of the comparative example.
[0051] XRD analysis showed that the grain size of the alloy was 23-27 nm when the Cu content was 0.6-1.3 atomic %. Comparative examples showed that when the Cu content was beyond this range, the amount of large atoms was relatively small, so the abnormal growth of grains could not be suppressed, and the grain size was over 35 nm, and the abnormal growth of grains was also a factor affecting the magnetic properties of the material.
[0052] Considering the thermal properties such as κ and λ, the magnetic properties such as Ps and Ss, and the crystal grain size, the preferred range of the Cu content was 0.6 to 1.3 atomic %. II.Verification of the role and control range of Nb The alloy compositions of the embodiments and comparative examples are shown in Table 4. The content of each element in the alloy components is expressed in atomic percent.
[0053] Table 4: Examples and Comparative Examples NanocrystalsThe alloy strip can be manufactured and subjected to heat treatment according to the scheme shown in FIG. 1, which includes the following steps: 21. Blend The blends were made according to the compositions of each embodiment and comparative example shown in Table 2. The industrial raw materials required were pure Fe, pure Cu, elemental Si, pure C, and Fe-B and Fe-P alloys, and the purity of the raw materials is shown in Table 1.
[0054] 22. Smelting The raw materials were weighed according to mass ratio and then put into a heating furnace (specifically, a medium frequency induction heating furnace) for melting. During the melting process, inert gas (such as argon) was introduced as a protective gas, and after melting, the materials were left to stand for 30 minutes to ensure that the composition of the molten steel was uniform without segregation. In one example, the total mass of the raw materials was 200 kg.
[0055] 23. Single-roll quenching for strip production The amorphous alloy strip is produced by the copper roll quenching method, that is, the molten steel is poured at 1400-1500°C and then quenched by the copper roll quenching method. Amorphous alloy strip was obtained and produced Amorphous alloy strip was wound into a loop. By way of example, the inner diameter of the loop may be 65 mm and the outer diameter may be 70 mm. In the embodiments herein, the thin strip may also be referred to as a strip.
[0056] 24.Heat treatment The amorphous alloy strips produced above were subjected to a heat treatment, which may also be referred to as a crystallization annealing treatment. NanocrystalsThe purpose is to promote the amorphous alloy to generate nanoscale crystal grains so that an alloy is produced. Specifically, during the heat treatment or crystallization annealing, a temperature 20-30°C higher than the first crystallization start temperature of the amorphous alloy is set as the heating target temperature. For example, the heating target temperature can be 420°C. For example, in order to ensure a uniform temperature increase, the heat treatment process of the amorphous alloy is divided into two stages. In the first stage, the temperature of the amorphous alloy thin strip is increased to 280°C and held at this temperature for 2 hours. In the second stage, the temperature of the amorphous alloy thin strip is increased to the heating target temperature at a rate of 30°C / min and held at this temperature for 30-40 minutes. Finally, the temperature is decreased at a rate of 50°C / sec, and after cooling to room temperature, Nanocrystals The alloy strip can be obtained. In order to prevent oxidation during the heat treatment, the heat treatment process is carried out in an inert gas (such as argon) atmosphere.
[0057] In this manner, strips of each embodiment or comparative example in Table 4 were produced. Using the XRD analysis described above, Nanocrystals We verified whether the alloy strip had a completely amorphous structure. The verification result is shown in Figure 3, which shows that only one broad diffuse scattering peak appeared at about 45°, which indicates that the alloy sample had a completely amorphous structure.
[0058] The results of the DSC analysis are shown in Table 4. Two obvious exothermic peaks appeared in the DSC curve of the sample, and the onset temperatures of the first and second exothermic peaks were T x1 and T x2 Based on these, ΔT x The area of the first exothermic peak can be calculated, so that the heat release Q1 of the alloy during the first crystallization can be calculated, and then the heat treatment characteristic parameter κ can be obtained.
[0059] [Table 4]
[0060] Table 4 shows the ΔT with different Nb contents. x The effect of increasing Nb in the range of 0.6 to 0.9 atomic percent on ΔT x does not show a clear linear relationship, and ΔT x was greater than 120°C. When the Nb content was less than 0.6 at.% or greater than 0.9 at.%, the heat treatment window ΔTx was obviously smaller. Based on the amount of heat Q1 released from the first crystallization peak, the heat treatment characteristic parameter κ was calculated, and the minimum value of κ was 1.39. After the ten strips were stacked, the maximum temperature T after the continuous temperature increase of the first crystallization of each embodiment was max The T of each embodiment was measured. max is the second crystallization temperature T x2 It can be seen that it did not exceed
[0061] From the comparative examples, it can be seen that when the Nb content was less than 0.6 atomic % or more than 0.9 atomic %, the values of λ were 3.33, 0.83, and 0.75, respectively. x The maximum value of T was 105°C, and the heat treatment characteristic parameter κ was 1.07 or less. max were all above the onset temperature of the second crystallization because the first crystallization released a large amount of heat, which triggered the second crystallization peak, leading to a continuous increase in temperature until the sample burned.
[0062] The amorphous alloy strip was subjected to heat treatment and performance test, and the specific process can be referred to the above. The performance test results are shown in Table 5. After heat treatment, the saturation magnetic induction and coercive force were measured, and then the magnetic properties of the loop (under the excitation condition of 1.5T / 50Hz) were measured by a BH tester. The iron loss per unit weight is Ps and the unit excitation power is Ss. The grain size was calculated using XRD analysis software.
[0063] [Table 5]
[0064] It can be seen from Table 5 that the saturation magnetic induction Bs of each embodiment was 1.75 T or more. When the Nb content was within the range of 0.6 to 0.9 atomic %, the iron loss Ps per unit weight of each embodiment was lower than that of the comparative example, and the unit excitation power Ss of each embodiment was also lower than that of the comparative example.
[0065] XRD analysis showed that the grain size was 23-30 nm when the Nb content was in the range of 0.6-0.9 atomic percent. The addition of Nb improved the thermal stability of the amorphous phase. When the Nb content in the alloy exceeded 0.6-0.9 atomic percent, the grains grew abnormally during the heat treatment of the alloy.
[0066] Considering the thermal properties such as κ and λ, the magnetic properties such as Ps and Ss, and the crystal grain size, the preferred range of the Nb content was 0.6 to 0.9 atomic %. III. Verification of the effect and control range of Cu to Nb ratio The alloy compositions of the embodiments and comparative examples are shown in Table 6. The content of each element in the alloy components is expressed in atomic percent.
[0067] The production and heat treatment of the amorphous alloy strip can be carried out as described above, but will not be repeated here. Using the XRD analysis described above, Nanocrystals We verified whether the alloy strip had a completely amorphous structure. The verification result is shown in Figure 4, which shows that only one broad diffuse scattering peak appeared at about 45°, indicating that the alloy sample had a completely amorphous structure.
[0068] The results of the DSC analysis are shown in Table 6. Two obvious exothermic peaks appeared in the DSC curve of the sample, and the onset temperatures of the first and second exothermic peaks were T x1 and T x2 Based on these, ΔT xThe area of the first exothermic peak can be calculated, so that the heat release Q1 of the alloy during the first crystallization can be calculated, and then the heat treatment characteristic parameter κ can be obtained.
[0069] [Table 6]
[0070] From Table 6, the ratio of Cu to Nb is x It was found that the increase in Nb in the range of 1≦λ≦1.4 affected ΔT x does not show a clear linear relationship, and ΔT x was greater than 120°C in all cases. When λ was less than 1 or greater than 1.4, ΔT x The heat treatment characteristic parameter κ was calculated according to the heat release amount Q1 of the first crystallization, and the minimum value of κ was 1.40.
[0071] After stacking the 10 strips, the maximum temperature T after the continuous temperature increase of the first crystallization of each embodiment max The T of each embodiment was measured. max is the second crystallization temperature T x2 It can be seen that it did not exceed
[0072] From the comparative examples, when the values of λ were 0.67, 0.67, and 1.73, respectively, ΔT x The maximum value of T was 105°C, and the heat treatment characteristic parameter κ was 1.09 or less. max were all above the onset temperature of the second crystallization because the first crystallization released a large amount of heat, which triggered the second crystallization peak, leading to a continuous increase in temperature until the sample burned.
[0073] The amorphous alloy strip was subjected to heat treatment and performance test, and the specific process can be referred to the above. The performance test results are shown in Table 7. After heat treatment, the saturation magnetic induction and coercive force were measured, and then the magnetic properties of the loop (under the excitation condition of 1.5T / 50Hz) were measured by a BH tester. The iron loss per unit weight is Ps and the unit excitation power is Ss. The grain size was calculated using XRD analysis software.
[0074] [Table 7]
[0075] From Table 7, it can be seen that the saturation magnetic induction Bs of each embodiment was 1.75 T or more. When λ was within the range of 1 to 1.4, the iron loss Ps per unit weight of each embodiment was lower than that of the comparative example, and the unit excitation power Ss of each embodiment was also lower than that of the comparative example.
[0076] XRD analysis showed that the grain size for each embodiment was 22-29 nm when λ was in the range of 1-1.4, and was larger when λ was not in the range of 1-1.4.
[0077] Considering the thermal and magnetic properties of the alloy, the preferred range of λ was 1 to 1.4. IV. Observation of the amorphous forming ability of different types of alloy compositions The thickness of the strip was used to characterize the amorphous forming ability of the corresponding alloy composition of the strip. Table 8 shows the amorphous forming ability of different kinds of alloy compositions.
[0078] [Table 8]
[0079] As shown in FIG. 8, the amorphous forming ability of each embodiment is obviously better than that of the comparative example, and the maximum thickness reaches 33 μm, which indicates that the amorphous forming ability of the strip produced according to the alloy composition limited by κ and λ is obviously better than that of other types of compositions.
[0080] In the above experiment, through verification based on different Cu contents, with the increase in Cu content, ΔT x It can be seen that the range of ΔT gradually increases, widening the width of the heat treatment window, which can prevent continuous temperature rise. By controlling the Cu content to 0.6-1.3 atomic %, ΔT x It can be guaranteed that ΔT is higher than 120℃. If the Cu content is not within this range, x clearly declined.
[0081] When the heat treatment characteristic parameter κ was 1.38 or more, the heat treatment window was obviously broadened, and T max ≦T x2 It can be ensured that the ΔT is 0.6-0.9 atomic %. Nb is a large atom, which can inhibit the precipitation of the main crystalline phase in the amorphous precursor, and can inhibit the excessive growth of atoms and control the grain size during the heat treatment process. The addition of Nb improves the thermal stability of the amorphous phase. By controlling the Nb content, when the atomic fraction of Nb in the P-containing alloy system is within the range of 0.6-0.9 atomic %, the ΔT x is greater than 110°C, which confirms that the requirements for heat treatment can be met. In addition, by configuring different ratios of Cu atoms to Nb atoms, a wide heat treatment window ΔT x It is confirmed that in order to ensure this, the ratio of Cu atoms to Nb atoms should be 1 to 1.4. When the ratio of Cu atoms to Nb atoms is 1 to 1.4, the heat treatment interval (i.e., ΔT x ) is broadened, which is beneficial for industrial heat treatment. In other words, a wider crystallization temperature zone (i.e., ΔT x) in order to form a nanocrystalline structure with small grain size and uniform distribution in the alloy, different ratios of the large atom Nb to other elements were used, and it was found that the minimum grain size was 23 nm when the ratio of Cu atoms to Nb atoms was 1≦λ≦1.4.
[0082] In addition, the saturation magnetic induction Bs of each of the above-mentioned embodiments was more than 1.75 T. By controlling the contents of main elements such as Cu and Nb, the crystal grain size after heat treatment could be controlled, and the crystal grain size was 20 to 30 nm.
[0083] In summary, in the embodiment of the present specification, the composition of elements is limited, and the composition range of the alloy is determined by the heat treatment characteristic parameters κ≧1.38 and 1≦λ≦1.4. The maximum amorphous forming ability of the produced strip is 33 μm, the heat treatment window is 120° C. or more, the Bs of the heat treated strip is 1.75 T or more, and the grain size of the nanocrystal is controlled to 20-30 nm. In addition, the Fe-based Nanocrystals The core loss of the alloy was less than 0.30 W / kg under the conditions of 50 Hz and 1.5 T.
[0084] It can be understood that the various numerical symbols included in the embodiments of this specification are merely for convenience of description and are not used to limit the scope of the embodiments of this specification.
Claims
1. An Fe-based nanocrystalline alloy, the atomic percentage of which is composed of elements represented by formula (1): ヲe (100-a-b-c-d-e-f) B a ウi b P c 3 d Cu e b f (1) An Fe-based nanocrystalline alloy, wherein 8≦a≦12, 0.2≦b≦6, 2.0≦c≦6.0, 0.5≦d≦4, 0.6≦e≦1.3, 0.6≦f≦0.9, and 1≦e / f≦1.
4.
2. The Fe-based nanocrystalline alloy according to claim 1, which is in the form of a continuous thin strip, and the strip thickness of the thin strip is 30 μm or more.
3. 2. The Fe-based nanocrystalline alloy of claim 1, wherein the temperature difference between the second crystallization onset temperature and the first crystallization onset temperature of the Fe-based nanocrystalline alloy is greater than 120°C.
4. 4. The Fe-based nanocrystalline alloy of claim 3, wherein a ratio of the temperature difference to a first calorific value is 1.38 or more, the first calorific value being a calorific value released from the Fe-based nanocrystalline alloy during a first crystallization process, the temperature difference is in degrees Celsius, and the first calorific value is in J / g.
5. The Fe-based nanocrystalline alloy according to any one of claims 1 to 4, wherein the Fe-based nanocrystalline alloy has a saturation magnetic induction of 1.75 T or more, a core loss per unit weight of the Fe-based nanocrystalline alloy under an excitation condition of 50 Hz-1.5 T is less than 0.30 W / kg, and a size of nanocrystalline grains in the Fe-based nanocrystalline alloy is 20 to 30 nm.
6. A method for producing an Fe-based nanocrystalline alloy according to any one of claims 1 to 5, comprising the steps of: (a) blending according to the atomic percentages of the elements shown in formula (1) and then smelting to obtain molten steel; (b) subjecting the molten steel to single roll quenching to obtain an initial strip; (c) heating the initial strip to a first preset temperature that is 20 to 30° C. higher than a first crystallization onset temperature of the initial strip; (d) maintaining said temperature for 30 to 40 minutes; and (e) cooling the initial strip to obtain the Fe-based nanocrystalline alloy; Including, ヲe (100-a-b-c-d-e-f) B a ウi b P c 3 d Cu e b f (1) wherein 8≦a≦12, 0.2≦b≦6, 2.0≦c≦6.0, 0.5≦d≦4, 0.6≦e≦1.3, 0.6≦f≦0.9, and 1≦e / f≦1.
4.
7. Heating the initial strip to a first preset temperature; heating the initial strip to a second preset temperature lower than the first preset temperature and holding the initial strip at said temperature for a preset time; and heating the initial strip from the second preset temperature to the first preset temperature at a first preset heating rate; The method of claim 6, comprising:
8. the second preset temperature is 280° C. and the preset time is 2 hours; 8. The method of claim 7, wherein the first preset heating rate is 30° C. / min.
9. 9. The method according to claim 6, wherein in step (e) the initial strip is cooled at a cooling rate of 50° C. / s.
10. A magnetic component made from an Fe-based nanocrystalline alloy according to any one of claims 1 to 5.
Citation Information
Patent Citations
ALLOY COMPOSITION, Fe-BASED NANO-CRYSTALLINE ALLOY, FORMING METHOD OF THE SAME AND MAGNETIC COMPONENT
JP2010070852A
ALLOY COMPOSITION, Fe-BASED NANOCRYSTALLINE ALLOY AND METHOD OF MANUFACTURING TYHE SAME, AND MAGNETIC COMPONENT
JP2011026706A